Open innovation as an important part of company’s innovation strategy - Skibinska, Olesia; Špaček, Miroslav, 1954-; Lyiubinets, Jaroslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
The aim of this thesis is to create an innovation strategy for R&D Department of a company that is operating in IT industry with a special focus on Open innovation. It consists of theoretical and practical part. Theoretical part presents modern literature research on innovation and outlines main concepts. Definition of innovation, its types and different approaches are described. Moreover, main principles of audit of Open innovation readiness and its measurement is presented. The last part is devoted to the description of IT industry and future trends. Practical part is devoted to company's analysis, audit of readiness to implement Open innovation approach and creation of innovation strategy for R&D Department.
Vedoucí práce: Miroslav Špaček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses